2014
DOI: 10.1007/s12185-014-1514-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of C-Myc gene-related aberrations in newly diagnosed myeloma with bortezomib/dexamethasone therapy

Abstract: Recent studies have suggested that c-Myc over-expression may be a factor indicating poor prognosis in multiple myeloma (MM), although c-Myc gene-related abnormalities, including translocation and gene amplification, have not been fully investigated in the novel agent era. Additional chromosome 8 may be considered as aggressive disease in the 1990s. To clarify the impact of these aberrations, we retrospectively analyzed newly diagnosed MM (NDMM) and relapsed/refractory MM (RRMM) with bortezomib and dexamethason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Studies in transgenic mouse models showed that even brief MYC inactivation is sufficient to induce tumor regressions (48) and that targeting MYC may destabilize apoptosis regulatory network and induce cell death in lymphoma (49). In multiple myeloma, a correlation between MYC overexpression (50) and poor response to treatment with bortezomib has been reported, and in mantle cell lymphoma, co-targeting MYC with (CPI203) was shown to overcome bortezomib resistance (51). While these studies show a correlation between MYC and resistance to proteasome inhibition, results from our experiments demonstrated the biological mechanism for MYC dependent resistance to proteasome inhibition, and moreover, how to circumvent these mechanisms to improve therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in transgenic mouse models showed that even brief MYC inactivation is sufficient to induce tumor regressions (48) and that targeting MYC may destabilize apoptosis regulatory network and induce cell death in lymphoma (49). In multiple myeloma, a correlation between MYC overexpression (50) and poor response to treatment with bortezomib has been reported, and in mantle cell lymphoma, co-targeting MYC with (CPI203) was shown to overcome bortezomib resistance (51). While these studies show a correlation between MYC and resistance to proteasome inhibition, results from our experiments demonstrated the biological mechanism for MYC dependent resistance to proteasome inhibition, and moreover, how to circumvent these mechanisms to improve therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…27 Unfavorable cytogenetics were defined as del(17p13), del(13q14), t(4;14), t(14;16), t(14;20), hypodiploidy, c-myc and chromosome 1 aberrations. 1,8,10,22,24,2731 The KPS was defined as normal (100%), mildly (90%), moderately (80%) or more substantially impaired (≤70%). Frailty and disability were assessed in order to get a more precise determination of patients’ physical condition.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Desiree Kirn, 3 Anja Seckinger, 1 Thomas Hielscher, 4 Martin Granzow, 3 Uta Bertsch, 1 Gerlinde Egerer, 1 Hans Salwender, 5 Igor W. Blau,…”
Section: Niels Weinholdmentioning
confidence: 99%